Świat zwierząt w anonimowym "Commentarii in Job" - Jóźwiak, Magdalena (Verbum Vitae, 2017)
Animals have been present in biblical and Christian symbolism from ancient times. Among the venerable exegetes who commented on the Books of the Holy Bible, questions were sometimes raised about the inherent features, and indeed the authenticity, of certain animals encountered in biblical passages. Animals were one of the motivations which led many of the Church Fathers and other Christian writers to embrace allegorical exegesis and symbolism. One can identify such practice in the reading of the ancient anonymous commentary on the Book of Job entitled Commentarii in Job (PL 26, 619-802). In this article we decided to analyze the treatments included in the Commentarii in Job about selected animals which appear in the Book of Job. Real animals that were discussed include: an ostrich, a snake, a rooster, a raven and a heron, and the fantastic ones are: an ant-lion, a unicorn, Behemoth and Leviathan. Fragments of the analyzed commentary are quoted as our own translation because – apart from our monograph and articles – there exist no other detailed studies, either in Polish or in international sources, that refer to the anonymous Commentarii in Job.